Digital Transformation, Fintech Utilization, Digital Financial Literacy, and Financial Sustainability of Culinary MSMEs - Nur Listiani; Siti Alliyah (Universitas Negeri Semarang, 2026)
This study aims to analyze the effect of digital transformation and fintech utilization on the financial sustainability of culinary micro, small, and medium enterprises (MSMEs), with digital financial literacy as a mediating variable. This research employed a quantitative explanatory approach involving 250 MSME owners and financial managers in Salatiga, Semarang, and Rembang. Data were collected through structured questionnaires and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results indicate that digital transformation and fintech utilization have positive and significant effects on digital financial literacy. Furthermore, digital financial literacy significantly influences the financial sustainability of culinary MSMEs. The findings also confirm that digital financial literacy plays an important mediating role in strengthening the relationship between technology adoption and financial sustainability. These results suggest that technology adoption becomes more effective when supported by adequate financial knowledge and digital skills. This study provides practical implications for policymakers and MSME practitioners to strengthen digital and financial literacy programs in order to enhance sustainable business performance.